Natural selection for genetic variants in sport: The role of Y chromosome genes in elite female athletes with 46,XY DSD - Ferguson-Smith, M. A.; Bavington, L. D. (Sports Medicine, 2014)
At present, it is widely assumed that hyperandrogenism in female athletes confers an unfair competitive advantage. This view is perpetuated in current regulations governing eligibility of female athletes with hyperandrogenism to compete, which identify testosterone levels in the male range as the critical factor. Detailed evidence is presented here for the first time that genes for stature (and possibly other genes) on the Y chromosome are responsible for the increased frequency of 46,XY disorder of sex development (46,XY DSD) among elite female athletes identified by eligibility tests. In many cases, androgens are non-functional or, alternatively, absent and therefore testosterone cannot be responsible for their athletic success. Genetic variation has a major role in the selection of individuals for training and success in competition; however, this variation is not grounds for determining who should compete in athletic events. There is no convincing evidence to support the view that hyperandrogenism is associated with performance advantage in female athletes. Current time-consuming regulations may lead to the unwelcome resurgence of innuendo in the media and coercion of female athletes into accepting gonadectomy and other treatments to which they might otherwise not have been subjected. These regulations should be withdrawn on the grounds that they are not supported scientifically, are discriminatory towards women and place some female athletes at risk of unnecessary and potentially harmful investigations. Improved understanding about genetic factors that lead to selection in sport should offer reassurance that women with hyperandrogenism possess no physical attribute relevant to athletic performance that is neither attainable, nor present in other women.